The Network Educational Administration Model of School under Nakhon Ratchasima Primary Educational Service Area Office - Bunradom, Chattupron; Bhoomkhokrak, Pikul; Phucharoean, Sakchai (Ratchaphruek Journal, 2020)
The purposes of this research were to: 1) Study the problems and needs assessment to the network educational administration of school; 2) to construct the network educational administration model of school; 3) to evaluate the network educational administration model of school under Nakhon Ratchasima Primary Educational Service Area Office. The research process was multiphase mixed method and consisted of four steps: Step 1 studying the network educational administration of school by interview; Step 2 studying the problems and needs assessment of the network educational administration of school by questioner from school administrator; Step 3 constructing the network educational administration model of school Area Office by focus group discussion; Step 4 constructing the manual and evaluate the use of the network educational administration. The instruments used for the research were questionnaire for the network educational administration of school condition and needs questionnaire for the network educational administration of school and suitability assessment form for evaluating that the model was appropriately and useful. The 297 samples were directors from 7 Nakhon Ratchasima Primary Educational Service Area Office, 5 experts form interview for evaluating that the model was appropriately. Data was collected from 9 experts in a focus group discussion. The obtained data were statistically analyzed by using the percentage, mean ( ), standard deviation (S.D.), and the content analyzed. Research results showed that 1) the network educational administration of school is needed among the schools under 7 Nakhon Ratchasima Primary Educational Service Area Offices, 2) the factors of the network educational administration model of school included of 6 elements: Share Vision; Structure and Administrator; communication and Learning Exchange; Innovation and Technology; Interaction, and Successful. 3) the constructed model was evaluated as appropriate, feasible, and useful at the highest level.